Biosecurity in pathology laboratories; COVID-19 pandemic. Narrative review - Walter Oqueli Vásquez Bonilla; Héctor Silva Cárcamo (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2020)
World Health Organization in its laboratory biosafety manual, classifies infectious agents into 4 risk groups ranging from level 1 to 4, these levels provide a series of procedures for the protection of laboratory personnel. After the risk assessment, SARS-CoV-2 is a pathogenic virus with a high mortality rate and a problem for public health, which has been classified in risk group level 3. Surgical pathology and cytology activities typical of pathology laboratories are carried out under a biosafety level 2, due to the classification of SARS-CoV-2 within risk group 3, it is necessary to reinforce security measures to protect personnel, these laboratories play an important role in histopathological diagnosis, providing information on the pathophysiology of the disease and the mechanisms that lead to the death of patients; which will make it possible to improve the treatment of the disease and design effective public health policies. This review describes the biosecurity measures that must be implemented in pathology laboratories during the current COVID-19 pandemic.